Impact of psychological profile on drug adherence and drug resistance in patients with apparently treatment-resistant hypertension. (2nd November 2018) - Petit, Géraldine; Berra, Elena; Georges, Coralie M.G.; Capron, Arnaud; Huang, Qi-Fang; Lopez-Sublet, Marilucy; Rabbia, Franco; Staessen, Jan A.; Wallemacq, Pierre; de Timary, Philippe; Persu, Alexandre
Abstract: Purpose: Patients with apparent treatment-resistant hypertension (a-TRH) are often poorly adherent to drug treatment and have an unusual personal history and psychological profile. The aim of this study was to identify predictors of drug adherence and drug resistance in a cohort of patients with aTRH, with emphasis on psychological characteristics. Methods: All patients with confirmed aTRH on standardized antihypertensive treatment were eligible. Drug adherence was assessed by drug dosages in urine using Liquid Chromatography coupled with tandem Mass Spectrometry (LC-MS/MS). Drug resistance was assessed by 24-hour ambulatory blood pressure adjusted for the number of antihypertensive drugs and for drug adherence. Psychological profile was assessed using a broad array of validated questionnaires. Results: The analysis included 35 consecutive patients. The proportion of adherent, partly adherent and totally non-adherent patients was 29, 40 and 31%, respectively. In regression analysis, independent predictors of poor drug adherence were recent hospital admission for hypertension, a lower ability to put things into perspective when facing negative events and a higher tendency to somatize, accounting for 51% of variability in drug adherence. Independent predictors of treatment resistance were a higher recourse to the strategies of blaming others and oneself, accounting for 37% of variability in drug treatment resistance. Conclusion: In patients with aTRH, poor adherence is frequent but does not entirely account for treatment resistance. Psychological characteristics appear as strong predictors of both drug adherence and drug resistance. Our results suggest that therapeutic drug monitoring and psychological evaluation should be an integral part of assessment of patients with aTRH.